Push button agriculture - Shawky, Hazem Fouda (Delve Publishing, 2019)
Push Button Agriculture examines various aspects into the developmentof agricultural field through vehicle technology andprovides a detailed information on automation in agriculture. Itis divided in 4 different sections where section 1 and 2 highlightssmart agriculture and automation in agriculture. Section 3 and 4are dedicated towards the use of robots and drones in agriculturalsector. Provide the reader the insights into the development ofagricultural sector and the role of institutions playing in this sector.